Report of the workshops on the Free Trade Area of the Americas, competitiveness and standards (ECLAC Port of SpainTT, 1999)
Contains the presentations made at a series of workshops in the countries of the Organization of Eastern Caribbean States (OECS) which were organized by the Economic Commission for Latin America and the Caribbean/Caribbean Development and Cooperation Committee (ECLAC/CDCC). Focuses on the Free Trade Area of the Americas (FTAA) process, the competitivenenss of firms and the issues of standards.
Keywords: FREE TRADE AREAS